Corn in Brejo Paraibano: Productive Transformations and Agricultural Challenges from 2000 to 2023 - Santos, João Paulo de Oliveira; Sousa, Valéria Fernandes de Oliveira; Bulhões , Luis Eugênio Lessa; Silva , João Henrique Barbosa da; Santos , Jobson Bruno de Oliveira; Dias , Leticia Alves; Melo , José Affonso Batinga de; Santos , Alex da Silva; Lima, Denilson da Silva de (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
Brazil is one of the largest corn producers and exporters in the world. In Paraíba, the Brejo Paraibano microregion is an important agricultural hub, benefiting from favorable soil and climate conditions for agriculture. However, some local factors still represent obstacles to production. In this context, considering the relevance of corn cultivation for local agriculture, the present study aimed to analyze the productive dynamics of corn in the Brejo Paraibano microregion, from 2000 to 2023. The data used in this research were obtained from the Municipal Agricultural Research database of the Brazilian Institute of Geography and Statistics (IBGE), to evaluate six variables related to corn production. Additionally, a Principal Component Analysis (PCA) and a Hierarchical Cluster Analysis (HCA) were used, the latter combined with a heatmap, in order to understand the interrelationships between the variables over time. Corn production in Brejo Paraibano showed significant fluctuations throughout the analyzed period, with a strong reduction in the planted and harvested areas. However, gains in productivity were observed. The PCA demonstrated that, for the studied region, larger quantities of corn produced are directly related to obtaining higher productivity, and not to the expansion of planted areas. Given the economic and cultural importance of corn for the microregion, it is necessary to implement efforts to improve the local yield of this crop, such as, for example, the technological development of production.